Given Up for You A Memoir of Love, Belonging, and Belief - White, Erin O. (The University of Wisconsin Press, 2018)
In this candid and revelatory memoir, Erin O. White shares her hunger for both romantic and divine love, and how these desires transformed her life. In the late 1990s, she spent Saturday nights with her girlfriend and Sunday mornings in Catholic confirmation classes. But when the Church closed its doors to her, she was faced with a question: What does a lesbian believer do with her longing for God? Given Up for You explores these yearnings with bittersweet conviction, plumbing the depths of heart and soul.